On “Auxiliary Precautions” (Publius) and Role of Federalism and Separation of Powers in the Evolution of European Integrations and Institutions - Bačić, Petar (Federalism as the Future of the Diverse EU?, 2025)
In the process of the development of the EU as an innovative, sui generis political and economic union of states, the forms of preventive constitutionalism – namely, federalism and the separation of powers – are shaped, modified and applied. This means that European constitutionalism, in order to nurture a “prudent attitude towards citizens”, must be understood as a policy that will follow Madison’s path and “compensate for a lack of better motives” with opposing and conflicting interests. As a consequence, both the theoretical and practical sides of the EU constitutional framework – if it indeed aspires to become an ever closer union among the peoples of Europe – must not only enable “the government to control the governed”, but also equally support and realise all existing and new “auxiliary precaution” measures, and checks and balances within government itself. In this article the author will focus precisely on the separation of powers and federalism as “auxiliary precautions” which every “good government” should take into account, including that of the EU.Keywords: State, European Union, Member States, Separation of powers, Federalism.